Rheological behavior of fire-fighting foams during their application – a new experimental set-up and protocol for foam performance qualification - Puget Aubin; Piquand Mathilde; Passedat Médric; Vercauteren Frank; Craenmehr Eric; Trimboli Joe; Fischer Hartmut (Applied Rheology)
The flow behavior of fire-fighting foams is an important factor in its performance as it largely determines how well and how fast the foam covers the burning fluid and seals it from oxygen. The flow characteristics, as well as the performance of such a foam is evaluated by a newly designed rheological cell and rheological experimental protocols mimicking a fire-fighting practice. Experiments are performed under conditions that apply while applying the foam (high shear of 10 s−1, continuous fresh foam feed, which limits draining and coarsening) and conditions that apply once the foam is deposited (low shear of 0.5 s−1, no foam feed allowing for draining and coarsening). This yields valuable insights. Very strong differences in flow behavior are observed changing from very well-flowing behavior on application to very viscous/stiff after deposition. Also, the shear-thinning character of foam flow was studied. After changing from a steady foam feed to a foam at rest situation, a transition period of complex flow behavior could be observed. This indicates that relaxation and restructuring processes of the foam bubbles that were deformed underflow are taking place. After this transition period, the effects of draining and coarsening become visible.